Surga Itu Tak Beratap: Refleksi atas Spiritualitas Kaum Non-Heteronormatif dan Gerakan Melawan Diskriminasi Berbasis Gender dan Seksualitas yang Dilakukan atas nama Agama - Agetta Putri Awijaya (Indonesian Journal of Theology, 2021)
Discrimination towards the non-heteronormative people, including in the mosques and churches, continues to happen. Along with that, particularly in Indonesia, the movements which fight for equality start to have new attention on faith and sexuality. This new wave shows that despite of the struggle related to gender and sexuality faced by our non-heteronormative fellows, there remains the need to defend their faith. The rejection, which is often based on religious values, does not fade their longing to be connected with God. In fact, our non-heteronormative fellows still strive to reach out to God through spiritual spaces outside the churches and refuse to believe the saying that they are “cursed” by God. Their faith does not only become the evidence of their yearning to devote, but also of God’s desire to embrace all creations in the communion with Him. Behind the struggle to cross the borders of patriarchal doctrines and discriminative interpretation of the Bible, there is a spirituality which recognize God’s presence and His involvement in the life of creation. This article tries to give an attention to the ideas which happen to be parts of non-heteronormative people and Beguine spirituality, as the latter was the pioneer of early emancipation movement, and then to construct a theological reflection which represents their spirituality. There is a hope that this article will contributes to the movements against the discrimination towards our non-heteronormative fellows, and that those movements will be regarded as an embodiment of our longing towards God and at the same time, the manifestation of the Triune God’s love which always moves to embrace all creations.